Medieval Hunting and Wood Management in the Buzzart Dykes Landscape. (1st August 2019) - Malloy, Kevin; Hall, Derek
Whilst research into medieval park landscapes has been limited in Scotland, recent efforts to enhance our understanding of the design, construction and functions of these structures through archaeological methods have been fruitful. This paper discusses the results of excavations at the site of Buzzart Dykes in Perthshire. As the site lacks historical documentation, little was known about how and when it was constructed and managed. Here we evaluate the modern interpretation of the enclosure as a medieval park used for hunting, and present evidence for additional economic utilisations that revolved around wood management. Excavations of the park bounds and associated longhouse structure clarify the landscape history of Buzzart Dykes, and demonstrate an effective methodology for studying park landscapes in Scotland.